2015
DOI: 10.1111/bjh.13447
|View full text |Cite
|
Sign up to set email alerts
|

Estimated pulmonary artery systolic pressure and sickle cell disease: a meta‐analysis and systematic review

Abstract: SummaryMany studies report estimated pulmonary artery systolic pressure (ePASP) in patients with sickle cell disease (SCD) screened by echocardiography. To better understand the prevalence and outcomes of elevated ePASP in clinically stable SCD patients, we conducted a random-effects meta-analysis. A total of 45 studies, representing 15 countries and including 6109 individuals, met our inclusion criteria. In most (70%) studies, elevated ePASP was defined by a tricuspid regurgitant velocity of 2Á5 m/s. The prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 64 publications
1
33
1
Order By: Relevance
“…Most previous studies worldwide have taken a cut-off TRV of ≥ 2.5 m/s as an indicator of pulmonary hypertension [3,1417]. When the latter cut off point was used, nineteen of our 94 patients (20.2%) would be considered as having PH.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most previous studies worldwide have taken a cut-off TRV of ≥ 2.5 m/s as an indicator of pulmonary hypertension [3,1417]. When the latter cut off point was used, nineteen of our 94 patients (20.2%) would be considered as having PH.…”
Section: Discussionmentioning
confidence: 99%
“…Among its most important pulmonary complications are acute chest syndrome (ACS) and pulmonary hypertension [2]. While most studies have used the non-invasive measurement of tricuspid regurgitant jet velocity (TRV) as an indicator of Pulmonary Hypertension (PH) with respective rates of 20–30% in sickle cell disease [3], using the invasive but "gold standard" method of right heart catheterization documented lower rates of 6.0–10.4% [46]. Pathogenesis of PH in sickle cell disease appears to be multifactorial, including: hemolysis induced endothelial dysfunction, chronic hypoxaemia, chronic thromboembolism, asplenia, intravascular sequestration of sickled red cells and iron overload [7].…”
Section: Introductionmentioning
confidence: 99%
“…The finding that TR jet velocity is improved in the group with chronic transfusion is of significant interest as TR jet velocity is a biomarker of disease severity, associated with an increased risk of having pulmonary hypertension defined by right heart catheterization, and an independent risk factor for early death. 9,10,12 In the second study, Almeida et al report that acute intravascular hemolysis induced by hypotonic water infusion in mice produces acute NO metabolism to nitrate and acute inflammation, as measured by decreased leukocyte rolling, and increased adhesion and extravasation. Interestingly, this effect is phenocopied by acute NO inhibition using 2-phenyl-4,4,5,5-tetramethylimidazoline-1-oxyl-3-oxide (PTIO) and blocked by an NO donor.…”
Section: 2mentioning
confidence: 99%
“…These results indicate the adverse impact of pulmonary vasculopathy on the heart, and strongly suggest a relationship to exercise capacity and death. This conclusion was further supported by a new meta-analysis of pulmonary artery pressure estimated by echocardiography [15]. This meta-analysis of 45 studies totaling 6109 patients across 15 countries found higher than normal estimated pulmonary artery systolic pressure (ePASP) in 21% of children and 30% of adults with SCD.…”
Section: Hemolytic Anemia Nitric Oxide and Vasculopathymentioning
confidence: 84%